Linear Regression Based Machine Learning Model for Cataract Disease Prediction - Premalatha, B.; Nataraj, Chandrasekharan (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Blindness and visual impairment have become major health problems today, with one major source of impairment being the formation of cataract disease. Cataract disease affects around 20 million individuals worldwide, with three out of every four being above the age of 60. A cataract is a clouding of the lens that impairs vision and can lead to blindness. Accurate and convenient detection of cataracts is essential for improving this condition. This paper presents a model based on linear regression to predict the presence of cataracts from images of the human eye. Experiments were conducted to validate the model. Various image processing techniques have also been used to perform image preprocessing and contrast enhancement, with patients notified about their eye health via SMS.
Keywords: Machine Learning Model; Linear Regression; Image processing; Feature Extraction; Cataract disease prediction